Effect of surface treatment and storage on the bond strength of different ceramic systems - Fernando Carlos Hueb de Menezes; Gilberto Antônio Borges; Thiago Assunção Valentino; Maria Angélica Hueb de Menezes Oliveira; Cecília Pedroso Turssi; Lourenço Correr-Sobrinho (Universidade Estadual de Campinas, 2015)
Aim: The aim of this study was to evaluate the micro shear bond strength of different ceramic systems - IPS Empress 2, Cergogold, In-Ceram Alumina and Cercon - and a dual luting agent. Methods: Twelve specimens of each ceramic were fabricated and divided according different surface treatments: Group 1: No additional treatment was applied to the ceramic surface; Group 2: Ceramics were etched with 9.5% hydrofluoric acid; Group 3: specimens treated with airborne particle abrasion for each ceramic system in accordance with manufacturer's instructions (n=20). The tests were performed after 24 h or after water storage for 6 months. Data were then assessed statistically using the 3-way ANOVA and the Tukey's test (P<0.05). Results: For Cergogold and IPS Empress 2 systems, the treatments performed with airborne particle abrasion and hydrofluoric acid showed no significant differences from each other, and both were superior to the groups without treatment. For Cercon and In-Ceram ceramics, no differences were found among the groups (P<0.05). When the surface was treated with hydrofluoric acid, the highest bond strength was found to IPS Empress 2 in the 6-month storage period (P<0.05). Conclusion: Lower bond strength values were only observed with IPS Empress 2 ceramic for the control group in the 6-month storage (P<0.05).